Associated injuries in electrical burns: a 2 year retrospective study in a tertiary care burns unit - Rao, Jagdeep; Bedi, Mitesh; Patil, Aditya; Barala, Vipin Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Electric burns are associated with a high degree of morbidity and mortality. The association of multiple injuries in burn patients further complicates the management problem. The injuries require prompt diagnosis and redressal for better outcomes. Methods: We decided to undertake a study to note characteristics of associated injuries in patients with electrical burns. A retrospective review was done of all patients admitted in Burn Unit of SMS Medical College and Hospital, Jaipur over a period of 2 years, who had sustained electric burns and had sustained associated injuries. Results: A total of 770 patients were admitted with electric burns over this duration. Associated injuries were noted in 4.15% of these patients. Young, male patients were more commonly affected, with a male to female ratio of 4:1. Conclusions: The incidence of associated injuries in electrical burns is not insignificant. A low threshold for suspicion is required in managing doctors to diagnose such injuries for optimal treatment and improved outcome in patients with electrical burns.